Is ultra low-dose CT with tin filtration useful for examination of SI joints? Can it replace X-ray in diagnostics of sacroiliitis? - Korcakova, Eva; Stepankova, Jana; Suchy, David; Hosek, Petr; Bajcurova, Kristyna; Pernicky, Jan; Mirka, Hynek (Biomedical papers, 2022)
Objectives. The first objective of our study was to determine the radiation exposure received by patients during tin-filtrated ultra-low-dose computed tomography (TFULDCT) of sacroiliac joints and to compare those to conventional X-ray doses. For comparison, we added a cohort examined by low-dose CT (LDCT) without tin filtration. The second objective was to compare the results of TFULDCT and X-ray in the detection of sacroiliitis. Methods. Our retrospective study covered 45 patients, who were examined for suspected axial spondyloarthritis (AxSpA). The first group underwent TFULDCT as well as conventional radiography (CR); the second group underwent LDCT only without tin filtration. Effective doses of TFULDCT, LDCT and CR were calculated by an experienced medical physicist. TFULDCT and CR were independently evaluated by three investigators, who decided on the presence or absence of rheumatoid inflammatory bone changes. The results were statistically evaluated. Results. In our cohort, the median effective dose for TFULDCT was 0.11 mSv, range (0.06-0.40 mSv), for LDCT 0.5 mSv (0.29-0.89 mSv), and for CR 0.25 mSv (0.06-1.87 mSv). We proved that TFULDCT produces a significantly lower percentage of uncertain results (23.3%; 95% CI: 11.3-41.6%) than CR (66.7%; 95% CI: 48.3-81.1%). Conclusions. Tin filtration helps to reduce CT radiation exposure to values lower than those resulting from CR. TFULDCT offers better overall diagnostic performance than CR. Our results prove that TFULDCT can replace CR in the diagnosis of sacroiliitis in the radiographical stage of AxSpA.
Keywords: radiation; computed tomography; tin filtration; sacroiliitis; axial spondyloarthritis